Irrigation Capital Requirements and Energy Costs - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1998)
This publication describes the economic advantages and disadvantages of irrigation in production agriculture.
MF836_1998_10
Keywords: MF836; Economics; MF